Evaluation of the strengths and weaknesses of Text Mining and Netnography as methods of understanding consumer conversations around luxury brands on social media platforms. - SAINI, CHITRA (2015)
The advent of social media has led to Luxury brands increasingly turning to social media sites to build brand value. Understanding the discussions that happen on social media is therefore a key for the marketing managers of luxury brands. There are two prominent methodologies which have been used widely in the literature to study consumer conversations on social media, these two methodologies are Text Mining and Netnography. In this study I will compare and contrast both these methodologies to evaluate their strengths and weaknesses in regards to analysing consumer conversations around four prominent luxury brands- Burberry, Chanel, Louis Vuitton and Michael Kors, on the social media site called Twitter.